Atrial septal defect and patent ductus arteriosus closure in an 8‐month‐old patient with Silver‐Russell syndrome. Issue 7 (19th July 2021) - Oda, Ryoma; Nakanishi, Keisuke; Kawasaki, Shiori; Amano, Atsushi
Abstract: We present a case of an 8‐month‐old boy with Silver‐Russell syndrome who had high pulmonary vascular resistance, atrial septal defect, and patent ductus arteriosus. He underwent cardiac surgery using cardiopulmonary bypass without any complications. Abstract : We present a case of an 8‐month‐old boy with Silver‐Russell syndrome who had high pulmonary vascular resistance, atrial septal defect, and patent ductus arteriosus. He underwent cardiac surgery using cardiopulmonary bypass without any complications.